Pathophysiology of traumatic bone marrow edema Pathophysiologie des traumatischen Knochenmarködems - Quack, V.; Schenker, H.; Beckmann, J.; Rath, Björn; Luering, C.; Tingart, M.; Betsch, Marcel (Unfallchirurg, 2015)
Background: Morphologically, bone marrow edema (BME) is an accumulation of fluid in the bone marrow. The BME is per se non-specific but can be identified at an early stage with magnetic resonance imaging (MRI). The underlying pathomechanism remains unclear. The BME can occur as an individual entity and as an accompanying condition of many diseases. The BME can be divided into three groups, ischemic, reactive and mechanical BME. Mechanical BME occurs after trauma or repetitive strain. Typical histological changes are present and there is no clear boundary between edema and microfracture. Some forms of trauma show BME in typical localizations. Both the trauma and the possible accompanying injuries can be indirectly indicated in this way in cases with an unknown trauma mechanism. Conclusion: The BME can be present as an isolated entity or as a comorbidity. For initiation of therapy, a comprehensive medical history and targeted diagnostics are indispensable. In some cases BME is indicative of the trauma mechanism and possible further accompanying injuries.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Accompanying injuries; Bone marrow edema; Bone stress; Diagnosis; Trauma mechanism